Shelter, ecophysiology and conservation status of Plectostylus araucanus (Pulmonata: Bothriembryontidae) in the fragmented Maulino Forest, central Chile - Rodrigo M. Barahona-Segovia; Andrea L. Riveros-Díaz; Sebastián Zaror; Ricardo Catalán; Juan Francisco Araya (Revista Mexicana de Biodiversidad)
Terrestrial mollusks are one of the least studied groups of terrestrial invertebrates, especially in the Neotropics. In Chile, there is scarce biological and ecological information about many genera, even though the group is quite diverse and occupies different habitats along the country. Plectostylus araucanus is the most recently described species and one of the few arboreal species found only in the coastal native forest of central-south of Chile. In this study, we recorded a new locality for P. araucanus in the Maule region and described ecological and physiological characteristics. The new locality is placed 204 km northwards of the type locality. Based on different records, Plectostylus araucanus is proposed as an endangered (EN) species under the distribution criterion of IUCN. Most of the specimens of P. araucanus were found living in tree cavities and away from the edge of native forest fragments. Physiological measures showed monthly differences, especially between some months of summer and fall and between months of the same season (i.e., summer). We discuss the implications of our results in the microhabitat selection, thermoregulation and habitat use by this tree snail, and the importance of this data in management and conservation for other native malacofauna.